2020
DOI: 10.3389/fcell.2020.00011
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles From Notch Activated Cardiac Mesenchymal Stem Cells Promote Myocyte Proliferation and Neovasculogenesis

Abstract: Cardiac mesenchymal stem cells (C-MSCs) are a novel mesenchymal stem cell (MSC) subpopulation derived from cardiac tissue, which are reported to be responsible for cardiac regeneration. Notch signaling is believed to aid in cardiac repair following myocardial injury. In this study, we have investigated the role of extracellular vesicles (EVs) from Notch1 engineered C-MSCs on angiogenesis and cardiomyocyte (CM) proliferation in ischemic myocardium. C-MSCs were isolated from Notch1 flox mice (C-MSC Notch1FF). No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…6e, f). EVs are small, membrane-bound vesicles released from cells that can transport cargo including DNA, mRNAs, microRNAs (miRNAs), and proteins [16,18]. The secreted EVs carrying specific miRNA from Givi-MPC likely facilitated angiogenesis [16].…”
Section: Givi-mpc Repopulated the Muscle Stem Cell Nichesmentioning
confidence: 99%
“…6e, f). EVs are small, membrane-bound vesicles released from cells that can transport cargo including DNA, mRNAs, microRNAs (miRNAs), and proteins [16,18]. The secreted EVs carrying specific miRNA from Givi-MPC likely facilitated angiogenesis [16].…”
Section: Givi-mpc Repopulated the Muscle Stem Cell Nichesmentioning
confidence: 99%
“…The authors suggested that platelet-derived growth factor D (PDGF-D), which was enriched in MSC-derived vesicles, was mainly responsible for the Akt exosome-mediated improvement of myocardial repair. A more recent study by Xuan and colleagues identified Notch1 as a potent modulator of angiogenesis and cardiomyocyte proliferation into ischemic mice hearts following coronary heart ligation [ 142 ]. The role of Notch1 signaling in inducing cardiac angiogenesis during ischemia and enhancing survival of cardiac cells is well established [ 143 ].…”
Section: Pre-clinical Evidence On the Use Of Msc-derived Exosomes mentioning
confidence: 99%
“…The role of Notch1 signaling in inducing cardiac angiogenesis during ischemia and enhancing survival of cardiac cells is well established [ 143 ]. The injection of MSC-derived EVs over-expressing Notch1 intracellular domain (NICD) in ischemic myocardium led to decreased infarct size, improved cardiac function, and increased arteriole density in the peri-infarct area, 1 month after AMI [ 142 ]. Moreover, Teng and coworkers indicated that the beneficial effect of MSC-derived exosomes on infarcted rat hearts is mainly dependent on their angiogenesis-promoting activity [ 144 ].…”
Section: Pre-clinical Evidence On the Use Of Msc-derived Exosomes mentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stromal cells (MSCs) are multipotent stem cells capable of differentiating into various cell types of the mesodermal lineage, including adipocytes, endothelial cells, fibroblasts, chondrocytes, osteoblasts, and myocytes ( Dominici et al, 2006 ), and possibly into non-mesodermal cell types, such as neural, pancreatic, hepatic, and gastric cells ( Oswald et al, 2004 ; Cislo-Pakuluk and Marycz, 2017 ; Luo et al, 2020 ; Xuan et al, 2020 ). They are a heterogeneous mesenchymal cell population, which resides in the stroma of various tissues and organs and expressing the membrane markers CD105, CD73, and CD90, but not HLA-DR, CD14, CD19, CD31, CD34, and CD45 ( Dominici et al, 2006 ; Nwabo Kamdje et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%